Pastoral care & counselling - Lynch, Gordon, 1968- (Ethics in practice., 2002)
Pastoral Care and Counselling provides an accessible framework for understanding the role of the pastoral care worker and the ethical dimensions of practice. In offering spiritual support and in helping others resolve their moral dilemmas, pastoral carers need to explore their own vision of humanity and what for them constitutes "the good life."